Efektivitas Bimbingan Kelompok Dengan Teknik Problem Solving Terhadap Kemampuan Berpikir Kritis Siswa Kelas XI MIPA 3 SMA Negeri Colomadu Tahun Pelajaran 2021/2022. - Zulfa, Anisah Nasih (MEDI KONS: Jurnal Prodi Bimbingan dan Konseling UNISRI Surakarta, 2023)
This study aims to determine the effectiveness of Group Guidance with Problem Solving Techniques on the Critical Thinking Ability of Class XI MIPA 3 SMA Negeri Colomadu in the Academic Year 2021/2022. This research is a quantitative experimental research with Pre Experimental Design One Group Pretest-Posttest Design research design. The population in this study were all students of class XI MIPA 3 SMA Negeri Colomadu in the academic year 2021/2022, totaling 33 people. The research sample uses a saturated sample, where the population is also used as a sample. Data collection techniques using questionnaires and documentation. The data analysis technique used is t-test. Based on the results of data analysis, the t-count value is 16.593. Furthermore, the t-count value was consulted with the t-table at d.b=N-1=32 and the significance levels of 5% and 1% were 2.037 and 2.738, thus the results of data analysis obtained that t-count was greater than t-table or 2.738<16,593>2,037. Thus Ho which states "Group Guidance With Problem Solving Techniques Is Ineffective Against Critical Thinking Ability of Class XI MIPA 3 SMA Negeri Colomadu in the Academic Year 2021/2021", is not proven and Ha states that "Group Guidance With Problem Solving Techniques is Effective on Ability Critical Thinking Students of Class XI MIPA 3 SMA Negeri Colomadu for the Academic Year 2021/2022 proved to be true both at the significance level of 1% and 5%. Keywords: Effectiveness, Effectiveness, Group Guidance, Problem Solving